Borrowing Costs and The Role of Multilateral Development Banks : Evidence from Cross-Border Syndicated Bank Lending - Gurara, Daniel; Presbitero, Andrea; Sarmiento, Miguel (Washington, D.C. : International Monetary Fund, 2018)
Cross-border bank lending is a growing source of external finance in developing countries and could play a key role for infrastructure financing. This paper looks at the role of multilateral development banks (MDBs) on the terms of syndicated loan deals, focusing on loan pricing. The results show that MDBs' participation is associated with higher borrowing costs and longer maturities---signaling a greater willingness to finance high risk projects which may not be financed by the private sector---but it is also associated with lower spreads for riskier borrowers. Overall, our findings suggest that MDBs could crowd in private investment in developing countries through risk mitigation.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet